Association of cardiac injury with hypertension in hospitalized patients with COVID-19 in China - Xiaofang Zeng; Anandharajan Rathinasabapathy; Dongliang Liu; Lihuang Zha; Xiangwei Liu; Yiyang Tang; Famei Li; Wenchao Lin; Zaixin Yu; Huiling Chen (Scientific Reports, 2021)
Abstract Outbreak of global pandemic Coronavirus disease 2019 (COVID-19) has so far caused countless morbidity and mortality. However, a detailed report on the impact of COVID-19 on hypertension (HTN) and ensuing cardiac injury is unknown. Herein, we have evaluated the association between HTN and cardiac injury in 388 COVID-19 (47.5 ± 15.2 years) including 75 HTN and 313 normotension. Demographic data, cardiac injury markers, other laboratory findings, and comorbidity details were collected and analyzed. Compared to patients without HTN, hypertensive-COVID-19 patients were older, exhibited higher C-reactive protein (CRP), erythrocyte sedimentation rate, and comorbidities such as diabetes, coronary heart disease, cerebrovascular disease and chronic kidney disease. Further, these hypertensive-COVID-19 patients presented more severe disease with longer hospitalization time, and a concomitant higher rate of bilateral pneumonia, electrolyte disorder, hypoproteinemia and acute respiratory distress syndrome. In addition, cardiac injury markers such as creatine kinase (CK), myoglobin, lactic dehydrogenase (LDH), and N-terminal pro brain natriuretic peptide were significantly increased in these patients. Correlation analysis revealed that systolic blood pressure correlated significantly with the levels of CK, and LDH. Further, HTN was associated with increased LDH and CK-MB in COVID- 19 after adjusting essential variables. We also noticed that patients with elevated either high sensitivity-CRP or CRP demonstrated a significant high level of LDH along with a moderate increase in CK (p = 0.07) and CK-MB (p = 0.09). Our investigation suggested that hypertensive patients presented higher risk of cardiac injury and severe disease phenotype in COVID-19, effectively control blood pressure in HTN patients might improve the prognosis of COVID-19 patients.